2020
DOI: 10.3390/ani10111973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dietary Inclusion of Buriti Oil on Lamb Performance, Carcass Traits, Digestibility, Nitrogen Balance, Ingestive Behavior and Blood Metabolites

Abstract: Buriti (Mauritia flexuosa L.) oil (BO) is a byproduct that can be incorporated into the diet of lambs, thus increasing the energy density. The study aimed to evaluate the optimum BO inclusion level in lamb diets. Sixty-five Santa Ines lambs were distributed in two completely randomized experiments with five treatments each (BO inclusion at 0 (control), 12, 24, 36 and 48 g/kg dry matter (DM) total). The BO supplementation to partially replace ground corn linearly decreased the nutrient intake and digestibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Furthermore, several trials have indicated that numerous feeding approaches can facilitate the deposition of n-3 LC PUFA in muscle tissues in lambs, resulting in healthier meat ( 16 , 24 , 37 42 ). The use of vegetable seed oils in ruminant diets was found to increase energy and the level of UFA deposited in meat ( 43 ). Thus, the resultant meat product had reduced levels of FA that were termed undesirable and enhanced levels that were characterized as beneficial to human health ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several trials have indicated that numerous feeding approaches can facilitate the deposition of n-3 LC PUFA in muscle tissues in lambs, resulting in healthier meat ( 16 , 24 , 37 42 ). The use of vegetable seed oils in ruminant diets was found to increase energy and the level of UFA deposited in meat ( 43 ). Thus, the resultant meat product had reduced levels of FA that were termed undesirable and enhanced levels that were characterized as beneficial to human health ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, fats and oils have been used in ruminant feed to increase the energy density of the diet. Then, the supplementation with buriti oil improves consumption, digestibility, and animal performance ( 85 ). However, the use of other oils, such as canola, sunflower, or castor oil, did not provide milk yield or increase the final bodyweight of the lambs ( 86 ).…”
Section: Discussionmentioning
confidence: 99%